TRiC/CCT chaperonin is required for the folding and inhibitory effect of WDTC1 on adipogenesis - Tang, Wen-Shuai; Cen, Xiang; Yao, Shan-Shan; Yin, Shu-Ting; Weng, Li; Zhao, Tong-Jin; Wang, Xu (Frontiers in Cell and Developmental Biology, 2023)
Obesity has become a global pandemic. WDTC1 is a WD40-containing protein that functions as an anti-obesity factor. WDTC1 inhibits adipogenesis by working as an adaptor of CUL4-DDB1 E3 ligase complex. It remains unclear about how WDTC1 is regulated. Here, we show that TRiC/CCT complex function as a chaperone to facilitate the protein folding of WDTC1 and proper function in adipogenesis. Through tandem purification, we identified the molecular chaperone TRiC/CCT complex as WDTC1interacting proteins. WDTC1 bound TRiC/CCT through its ADP domain, and the TRiC/CCT complex recognized WDTC1 through the CCT5 subunit. Disruption of the TRiC/CCT complex by knocking down CCT1 or CCT5 led to misfolding and lysosomal degradation of WDTC1. Furthermore, knockdown of CCT1 or CCT5 eliminated the inhibitory effect of WDTC1 on adipogenesis. Our studies have uncovered a critical role of TRiC/CCT in the folding of WDTC1 and expanded our knowledge on the regulation of adipogenesis.